Low Temperature Synthesis of 3d Metal (Fe, Co, Ni, Cu)-Doped TiO2 Photocatalyst via Liquid Phase Deposition Technique - Mitsuhiro Honda; Yusaku Yoshii; Nobuchika Okayama; Yo Ichikawa (Sustainable Chemistry)
The titanium dioxide (TiO2) photocatalyst is an important semiconducting material that exhibits environmental purification functions when exposed to light. Elemental doping of TiO2 is considered an important strategy to improve its photocatalytic activity. Herein, we have achieved the low-temperature, atmospheric-pressure synthesis of anatase TiO2 particles with doping of 3d metals (Fe, Co, Ni and Cu) based on the liquid phase deposition technique. All products prepared by adding 3d metals were found to consist of TiO2 crystals in the anatase phase with a fine protruding structure of about 40 nm on the surface, as was the case without the addition of metal ions. Iron and copper were observed to be incorporated at higher concentrations than cobalt and nickel, with an elemental addition of up to 4 at% and 1 at%, respectively, when 10 mM iron and copper nitrate were applied. Such doping efficiency could be explained by the difference in ionic radius and chemical stability. A narrowing of the optical band gap with doping elements was also observed, and it was found that optical sensitivity could be imparted down to the visible-light region of 2.4 eV (Fe: 4 at% addition). Furthermore, the 3d metal-doped TiO2 demonstrated in this study was shown to exhibit photocatalytic methane degradation activity. The amount of methane degradation per unit area of the microparticles was twice as great when iron and copper were added, compared to the undoped counterpart. It has been demonstrated that the strategy of doping TiO2 with 3d metal ions by low-temperature synthesis methods is effective in enhancing carrier dynamics and introducing surface active sites, thus increasing methane degradation activity.